2‐Deoxyribose‐5‐phosphate aldolase from Thermotoga maritima in the synthesis of a statin side‐chain precursor: characterization, modeling and optimization. Issue 6 (15th March 2019) - Švarc, Anera; Findrik Blažević, Zvjezdana; Vasić‐Rački, Đurđa; Szekrenyi, Anna; Fessner, Wolf‐Dieter; Charnock, Simon J; Vrsalović Presečki, Ana
Abstract: BACKGROUND: Producing statin side‐chains by sequential aldol condensation catalyzed by 2‐deoxyribose‐5‐phosphate aldolase (DERA) (EC 4.1.2.4) is the best‐known and most promising synthetic route. The advantage of this process is the formation of two stereocenters in a single step starting from inexpensive achiral components, acetaldehyde and chloroacetaldehyde. The limitation for the industrial‐scale application is enzyme inactivation caused by substrates as well by the intermediate produced by single aldol addition. RESULTS: The DERA enzyme from Thermotoga maritima (DERA Tm ) was investigated extensively in this work. The influence of aldehydes on DERA Tm stability was studied in detail. Mathematical models in different reactor configurations were developed based on experimentally determined kinetic parameters of all reactions included in the synthesis of statin side‐chain. Models also included enzyme inactivation by all compounds with negative impact on its stability. Mathematical model‐based optimization enabled optimization of process conditions and reactor configuration. The fed‐batch reactor proved to be the most suitable choice achieving product concentration of 78 g L −1, productivity of 56 g L day −1 and yield of 95% under an optimal condition. CONCLUSION: The validated mathematical model and applied methodology can be exploited for further process improvement and for process design of similar systems. © 2019 The Authors. Journal of Chemical Technology & Biotechnology published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.